Variations in local heavy metal concentrations over the last 16,000 years in the central Atacama Desert (22°S) measured in rodent middens - Vargas-Machuca, Barbara D.; Zanetta-Colombo, Nicolas; De Pol Holz, Ricardo Hernán; Latorre, Claudio (My University, 2021)
Mining is a major industry in the Atacama Desert, one of the world's leading regions for copper and other minerals. Intense industrialization of copper mining in the mid-twentieth century has likely led to significant environmental pollution through the deposition of heavy metals in the hyperarid Atacama, but how heavy metal pollution has changed over time in arid regions have rarely been assessed. Here, we analyzed both modern and ancient fecal pellets frompaleomiddens collected in the central Atacama for heavy metals and by comparing current heavy metal concentrationswith pre-industrial ones, we establish ecological baselines for such pollution. Sixteen paleomiddens spanning the last 1000 years from multiple localities in the eastern Calama Basin (22 degrees S) show elevated concentrations of Cu and As in modern compared to older middens, and that heavy metal, alkali metals and alkaline earth metals showpositive correlationswith each other. Heavymetals also tend to be higher in paleomiddens collected along perennial rivers in comparison to those collected fromsurrounding ranges, irrespective of sample age. Twenty paleomiddens spanning the last c. 16,000 years from a single locality (El Hotel) between the Calama and San Pedro de Atacama basins were used to establish long termvariations in plant communities and associated heavy metals since the last glacial termination. Results show that heavy metal concentrations including Cr, Mo and B vary over time and tend to be higher in paleomiddens for which Cactaceae are more abundant whereas those dominated by annuals show less of an effect from trace metals. Our results imply that climate change-driven plant community composition plays a key role in explaining how contamination varies in these desert ecosystems and show that paleomiddens are a unique and unexplored source for understanding how heavymetals vary over time. Given their ubiquity in many of the world's arid regions, they can be used to establish long-term ecological baselines to compare against human alterations. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: rodent middens; heavy metals; pollution; ecological baselines; atacama 01sert